Using dimethylsulfonium to identify readers of methylation - Li, Xiang; Li, Xiang David (Nature chemistry, 2024)
Decoding a post-translational modification requires the identification of its ‘reader’ proteins. Now a method can covalently trap the readers of lysine methylation using dimethylsulfonium as a methyllysine-mimicking ‘warhead’ to crosslink the tryptophan residues inside the binding pocket.